Impact of Taxpayer Demographics, Digitalization of Tax Reporting and Fiscus Services in Increasing Individual Taxpayer Awareness and Compliance - Sukmoputro, R. Panji Pinilih; Mahayuni, Luh Putu (International Journal of Economics Development Research (IJEDR), 2024)
This research focuses on individual taxpayers, who are often overlooked in tax studies that focus more on companies. Thus, this research offers a new perspective in analyzing individual taxpayer compliance in the digital era. This study provides empirical testing of tax service quality and its relationship with taxpayer compliance, which previously may not have been explored in depth with quantitative methods and was linked to demographic variables and digitalization. The research was conducted on individual taxpayers at the Pratama Gianyar-Bali Tax Service Office (KPP). The number of respondents used as research samples was 180 people. The data collection technique uses a questionnaire. This research uses SEM (structural equation modeling) Partial Last Square (PLS) data analysis techniques with SmartPLS 4.0. The research results show that demographic factors do not significantly influence taxpayer awareness and compliance. Meanwhile, digitalization of tax reporting and tax authorities services has a positive and significant influence on taxpayer awareness and compliance. The results of this research also show that taxpayer awareness is able to partially mediate the influence of demographics and digitalization of tax reporting on taxpayer compliance.